Rambu Solo Funeral Tradition in Toraja: A Legal, Ethical and Economic Model for Cultural Tourism - Muthoifin; Muhammad Iqbal; Nuha; Aboubacar Barry; Rezaul Islam (International Journal of Law and Society, 2026)
The Rambu Solo funeral tradition of the Torajan people constitutes a prominent form of cultural tourism that raises unresolved normative tensions between religious law, cultural preservation, and economic development. Although extensively examined from anthropological and tourism perspectives, limited scholarly attention has been devoted to its evaluation within Islamic legal discourse, particularly regarding normative boundaries and ethical engagement in non-Islamic ritual environments. This study addresses this gap by examining Rambu Solo through a primarily normative Islamic legal framework, informed by ethical, socio-legal, and socio-economic perspectives. Employing a qualitative normative literature review, the study is grounded in the principles of usul al-fiqh and maqasid al-shariah, with socio-legal and economic aspects functioning as analytical contexts. The analysis combines textual examination of classical fiqh sources with contemporary Islamic legal scholarship and anthropological studies on Torajan culture. Legal reasoning applies juristic classification (ahkam taklifiyyah) alongside maqasid-based evaluation to assess cultural practices according to the criteria of tawhid, hurmat al-mayyit, and public interest (maslahah). The findings indicate that social and economic dimensions of Rambu Solo, including communal solidarity and local economic welfare, are normatively permissible and ethically consistent with Islamic principles. In contrast, ritual elements involving ancestral veneration or symbolic invocation of spirits exceed permissible boundaries due to conflict with Islamic monotheism. The study proposes a balanced legal–ethical model distinguishing permissible cultural participation from prohibited ritual engagement. Theoretically, this research advances Islamic legal studies by extending normative analysis to cultural tourism governance and by offering guidance for policymakers and Muslim communities developing tourism practices.